The relationships between fish size and otolith dimensions in the common sole (Solea solea (Linnaeus, 1758)) captured in the Northeastern Mediterranean - Basusta, Asiye; cetinkaya, Burak; Basusta, Nuri (Wiley, 2020)
Fish specimens were captured by a commercial bottom trawler at a depth of 50-80 m from Iskenderun Bay (Hatay, Turkey) between December 2017 and May 2018. The bottom trawl gear used was equipped with a 44 mm stretched mesh size net at the cod-end. Blind side and eyed side otolith lengths (OL), otolith breadths (OB) and otolith weights (OW) were measured from each specimen to the nearest 0.001 mm and 0.0001g respectively. A total of 110 fish (43 females and 67 males) were collected. Total length ranged from 20.8 to 28.2 cm and 68.0 to 166.1 g (males) and 21.1 to -28.5 cm and 74.5 to 201.4 g (females). The coefficients of determination between fish weight and otolith weight, and total length and otolith weight (sexes combined) were found as R-2 = .7694 (0.77) and R-2 = .6274 (0.63), respectively. A moderate positive relationship between the total length-otolith dimensions, and fish weight-otolith dimensions, was also demonstrated.
2nd International Fisheries Symposium (IFSC) -- NOV 04-08, 2018 -- Girne, CYPRUS
Keywords: Length